2020
DOI: 10.1111/opo.12722
|View full text |Cite
|
Sign up to set email alerts
|

One‐year results of 0.01% atropine with orthokeratology (AOK) study: a randomised clinical trial

Abstract: Purpose To report the 1‐year results of an investigation into whether there is an additive effect between 0.01% atropine and orthokeratology (ortho‐k), in a single‐masked, two‐arm, randomised controlled trial: Combined Atropine with Orthokeratology (AOK) for myopia control study (ClinicalTrials.gov number: NCT02955927). Methods Chinese children aged between 6 and 11 years with 1.00–4.00 D of myopia, astigmatism <2.50 D, and no more than 1.00 D anisometropia, were randomly assigned either to an AOK group or ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 44 publications
9
91
0
Order By: Relevance
“…328 A recent study showed an additive effect between 0.01% atropine and ortho-K over 1 year, with mean axial elongation in the atropin with orthokeratology group 0.09 mm/year slower than that in the ortho-K group. 329 A review reported that all included studies improved myopia control by the synergistic effect of ortho-K with low-dose atropine, compared with orthokeratology treatment alone. 330 Another pharmacological and optical combination therapy is the use of multifocal spectacles with 0.5% atropine.…”
Section: Combination Of Interventionsmentioning
confidence: 99%
“…328 A recent study showed an additive effect between 0.01% atropine and ortho-K over 1 year, with mean axial elongation in the atropin with orthokeratology group 0.09 mm/year slower than that in the ortho-K group. 329 A review reported that all included studies improved myopia control by the synergistic effect of ortho-K with low-dose atropine, compared with orthokeratology treatment alone. 330 Another pharmacological and optical combination therapy is the use of multifocal spectacles with 0.5% atropine.…”
Section: Combination Of Interventionsmentioning
confidence: 99%
“…It may be related to that the follow-up time of this study is only one month, while other studies are more than one year. Subgroup 2 (midium myopia"-3~ -6D") showed that the heterogeneity decreased from 54% to 0% after excluding Tang 2020, [29] but the results remained unchanged. (Table 3 ).…”
Section: Sensitivity Analysismentioning
confidence: 94%
“…There were 6 studies with baseline SER ranging from -1 to -3D ,146 patients in AOK group and 149 patients in ortho-k group. [24][27][29] [31]1 The combined results showed that the WMD in the low myopia subgroup was -0.10 mm (95% CI, -0.14, -0.05), which represented that the mean axial elongation of AOK was 0.10 mm shorter than that of ortho-kwithin baseline diopter -3D.There were 3 studies [24][27] [29] with baseline SER ranging from -3 to -6D,62 patients in AOK group and 62 patients in ortho-k group. The combined results showed that the WMD of the midium myopia subgroup was -0.04mm (95% CI, -0.11, 0.03).…”
Section: Change In Almentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the titles and abstracts of all articles and excluded 12 articles; full texts and data integrity were also reviewed and 15 were further excluded. Finally, studies that met all inclusion criteria were included in this meta-analysis [13][14][15][17][18][19][20][21][22]. Figure1 showed the selection process of eligible articles.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%